Dynamics of an Introduced Caribou Population - Heard, Douglas C.; Ouellet, Jean-Pierre (ARCTIC, 1994)
Caribou (Rangifer tarandus groenlandicus) were hunted to extinction on Southampton Island (Northwest Territories, Canada) by 1953. In 1967, 48 caribou were captured on neighbouring Coats Island and released on Southampton Island. We documented the population dynamics, group size and composition, and distribution of caribou from introduction to 1991, based on aerial and ground survey data. The number of one-year-old caribou grew from 38 in 1967 to 13 700 (SE = 1600) in 1991. The corresponding annual growth rate was 27.6%, with no indication of any decline in the rate with increasing population density. Contrary to models describing the irruption of ungulates, the population dispersed rapidly after introduction to use all suitable habitats. Southampton caribou did not show high winter mortality in some years as did caribou on neighbouring Coats Island, where caribou density was higher, suggesting that the effect of adverse weather on the dynamics of northern insular caribou populations is dependent on animal density.Key words: caribou, Rangifer, population dynamics, irruption, distribution, Northwest Territories Dans l'île Southampton (Territoires du Nord-Ouest [Canada]) le caribou (Rangifer tarandus groenlandicus) a fait l'objet d'une chasse jusqu'en 1953, date de son extermination. En 1967, on a capturé 48 caribous dans l'île Coats avoisinante et on les a relâchés dans l'île Southampton. On documente la dynamique, la taille et la composition des groupes ainsi que la distribution du caribou depuis son introduction jusqu'en 1991, en s'appuyant sur des données obtenues à l'aide de relevés aériens et terrestres. Le nombre des caribous âgés d'un an et plus est passé de 38 en 1967 à 13 700 (erreur-type = 1600) en 1991. Le taux de croissance annuel correspondant était de 27,6 p. cent et ne comportait aucune indication dénotant une baisse du taux accompagnant une augmentation de la densité de population. Contrairement à des modèles décrivant l'explosion du nombre d'ongulés, la population de caribous s'est dispersée ...